Highly disordered cobalt oxide nanostructure induced by sulfur incorporation for efficient overall water splitting. (May 2020) - Yu, Xingxing; Yu, Zi-You; Zhang, Xiao-Long; Li, Peng; Sun, Bing; Gao, Xiaochun; Yan, Kang; Liu, Hao; Duan, Yu; Gao, Min-Rui; Wang, Guoxiu; Yu, Shu-Hong
Abstract: Exploitation of cost-efficient active electrocatalysts for oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) plays a significant role for scalable electricity-to-hydrogen energy conversion. Crystalline transition metal oxides as the promising non-noble catalysts, however, are often suffering from the large excess overpotential and unsatisfactory performance. To boost their intrinsic catalytic property, we report here an incorporation of electronegative sulfur into crystalline cobalt oxide (S-CoOx ) to create structural disorder via a facile room-temperature ion exchange strategy. Compared with its crystalline form, the disorder in S-CoOx catalyst enables the increased low oxygen coordination and rich defect sites, which endows S-CoOx a superior catalytic activity for both OER and HER in alkali. Intriguingly, a water electrolyser adopting S-CoOx as both OER and HER electrode catalysts requires mere 1.63 V to reach a current density of 10 mA cm −2 in 1 M KOH. This work highlights the effectiveness of designing high-performing electrocatalysts for water electrolysers based on disordered structural materials. Graphical abstract: Image 1 Highlights: The structurally disordered S-CoOx catalyst was synthesized via a facile room-temperature sulfur ion exchange strategy. The structurally disordered catalyst shows increased low oxygen coordination and more defect sites. Experimental and DFT calculation results reveal that a preferable electronic state was generated for the disorderedS-CoOx catalyst. This novel structurally disordered strategy enables the S-CoOx catalyst a superior catalytic activity for both OER and HER in alkaline electrolyte.